Optimization of Sub-Provider Evaluation Using ANP Approach and CSI Modification at PT XYZ - Aqila Yusriyya Hanun; Wiwik Handayani; Raden Johnny Hadi Raharjo (Finance : International Journal of Management Finance, 2025)
This study aims to develop on internal performance evaluation model for sub-providers at PT XYZ using the Analytic Network Process (ANP) and Modified Customer Satisfaction Index (CSI), called the Internal Performance Index (IPI). The main problem addressed in the delay of sub-providers in handling customer complaints, which affects customer satisfaction and operational efficiency. ANP is applied to determine the weighted interdependent criteria, while IPI assesses efficiency, compliance, and internal reporting accuracy. Data were collected through interviews and questionnaires involving five experienced internal respondents. The analysis resulted in a ranking of sub-providers based on weighted indicators. This finding contributes to improving the objective and systematic partner evaluation process and provides strategic recommendations for management in selecting the most appropriate partners.